Biochemical and molecular assessment of the superoxide dismutase (SOD) antioxidant enzyme regulation within Medicago truncatula root in response to iron deficiency - Nadia Kallala; Wissal M'sehli; Manel Chaouachi; Karima Jalali; Ghassen Abid; Haythem Mhadhbi (PLoS ONE, 2025)
Iron (Fe) deficiency is a major nutritional stress affecting plant growth and metabolism. This study was conducted on three Medicago truncatula genotypes (TN8.20 and A17 as tolerant and T1.11 as a sensible genotype) cultivated in optimal and Fe-deficient conditions. Assessment of Fe deficiency effects was performed on some physiological and biochemical parameters with a particular focus on superoxide dismutase (SOD) activities and genes expression in roots. Our data showed that the sensitive genotype TN1.11 was more affected by Fe starvation compared to A17 and TN8.20. Overall, the relatively higher tolerance of A17 and TN8.20 to Fe deficiency was positively correlated to their ability to maintain higher plant biomass, Fe content, Fe use efficiency, Cu and Zn contents in roots. The oxidative stress associated with Fe-deficiency was evidenced by increased roots hydrogen peroxide (H 2 O 2 ) levels, especially in TN1.11 genotype. In contrast, Assessment of SOD activity in roots revealed a significant increase in Cu/ZnSOD and MnSOD activities under Fe-deficient conditions, particularly in TN8.20. Gene expression analysis showed differential regulation of FeSOD , Cu/ZnSOD and CHSOD genes in response to Fe deficiency. Notably, TN8.20 exhibited upregulation of Cu/ZnSOD and down regulation of CHSOD under Fe-deficient conditions. TN8.20, which showed the highest SOD activities and gene expression levels, was identified as the most tolerant genotype. These findings highlight the physiological and molecular responses of Medicago truncatula to Fe deficiency and emphasize the comparative leaf-root analyses, revealing that SOD related genes in roots may serve as useful molecular markers for selecting Fe-deficiency-tolerant genotypes to cope with oxidative stress and nutrient imbalances.